Constituent and microstructure concentration indexes for microsedimentological analysis in thin sections - Paisani, Julio Cesar; Manica, Rafael (Revista Brasileira de Geomorfologia, 2025)
The starting point for explaining a geomorphological process relies on describing the fundamental properties of the morphology-forming materials (aggradational morphogenesis). Microsedimentological analysis has been used for decades to address issues within Quaternary Geomorphology and slope processes. However, the descriptive criteria for thin sections concerning the abundance of coarse fraction constituents and microstructures remain qualitative and/or based only on absolute percentages. Nonetheless, a more comprehensive, quantitative criterion, which also considers the area of occurrence in the calculation can provide greater descriptive objectivity. Thus, this study presents a constituent concentration index (Cci) and microstructure concentration index (Mci) for the coarse fraction to enable comparison among the laminae ("strata") of a given thin section. These indices mitigate subjectivity in describing the proportionality of coarse fraction constituents and their respective sedimentological microstructures relative to the analyzed area. They are also readily available to researchers and can be applied to a wide range of constituents and microstructures.